Application of Deep Learning-Based Problem Based Learning to Increase Motivation and Critical Thinking of Elementary School Students - Ain, Nurul; Kurniawati, Resta Eka; Zuhro, Luluk Faridatus (Actual Insight, 2025)
This study aims to describe the application of the Problem Based Learning model based on the Deep Learning approach to improve learning motivation and critical thinking ability of grade V elementary school students. The research was motivated by the low motivation and student involvement in learning, particularly in understanding the importance of preserving regional food and beverages. The method used was Classroom Action Research conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 27 students of grade 5B at Bandungrejosari I Public Elementary School Malang City. Data were collected through observations, learning motivation questionnaires, and critical thinking ability tests, then analyzed descriptively and quantitatively. The results showed that the application of Problem Based Learning integrated with the Deep Learning approach effectively improved students’ motivation and critical thinking skills. Learning completeness increased from 33.33% in the pre-cycle to 66.66% in the first cycle, and reached 92.59% in the second cycle, with an average final score of 85. Students became more active, reflective, and able to connect learning materials with local cultural contexts. This study not only confirms the theoretical effectiveness of integrating Problem Based Learning and Deep Learning in developing 21st-century competencies in elementary education but also offers a practical, contextual, and participatory learning strategy alternative.